Anti-hyperlipidemic effects of Rhizoma Coptidis alkaloids are achieved through modulation of the enterohepatic circulation of bile acids and cross-talk between the gut microbiota and the liver. (August 2017) - He, Kai; Ma, Hang; Xu, Heshan; Zou, Zongyao; Feng, Min; Li, Xuegang; Ye, Xiaoli
Highlights: Rhizoma Coptidis (RC) alkaloids exert liver–gut axis modulating activities. RC alkaloids regulate the enterohepatic circulation of bile acids. RC alkaloids reverse the abundance of gut microbes in hyperlipidemic mice. Abstract: Molecular and microbiome studies were employed to uncover the mechanisms underlying the cholesterol lowering effects of RC alkaloids. Hyperlipidemic mice were treated with RC alkaloids for 35 days. After treatment, bile acid levels in serum, liver and feces were investigated. Key targets involved in enterohepatic circulation of bile acids were evaluated. 16S rDNA analysis was used to study the change of gut microbiota in mice. The up-regulated CYP7A1 and BSEP in mouse liver accelerated the synthesis and transportation of bile acids. Bile acids were reabsorbed due to the increased ASBT in mouse ileum. The down-regulated claudin-1 and occludin in ileum contributes to enlarged fetal excretion of bile acids. RC alkaloids treatment restored the disrupted gut microflora in hyperlipidemic mice. These findings present new evidence supporting a key role for RC alkaloids as a regulator of liver–gut axis in hyperlipidemic mice.